Persepsi Petani Padi Terhadap Pupuk Organik Berbasis Serasah di Kabupaten Karanganyar: Persepsi Petani Padi Terhadap Pupuk Organik Berbasis Serasah di Kabupaten Karanganyar - Wahyu Widayat; Norbertus Citra Irawan; Adhisty Puri Damayanti; Dewi Rahmawati Intan Permatasari; Teguh Supriyadi; Haryuni; Agung Prasetyo; Mahananto; Suswadi (JURNAL ILMIAH AGRINECA, 2026)
This study aims to analyze rice farmers' perceptions of Komsah, a litter-based organic fertilizer, in Karanganyar Regency, Indonesia. A quantitative descriptive method was employed, with a sample of 42 rice farmers selected through purposive sampling. Data were collected through interviews using structured questionnaires and analyzed using a Likert scale (1–5) based on Rogers' five innovation attributes: relative advantage, compatibility, complexity, trialability, and observability. The data were analyzed descriptively, and validity and reliability tests were conducted. The results indicate that farmers' perceptions of Komsah organic fertilizer remain generally in the undecided category across most dimensions. Farmers acknowledged that Komsah offers technical benefits, is compatible with rice farming practices, is easily accessible for trial, and provides positive environmental impacts. However, they remain doubtful about its economic advantages, its compatibility with the habitual use of chemical fertilizers, and its efficiency in terms of cost, labor, and time application. The observability dimension received the highest rating, as the environmental benefits and knowledge enhancement were more readily perceived compared to economic benefits, which have yet to be clearly demonstrated. The findings imply that although farmers recognize the technical and environmental benefits of Komsah, economic considerations and uncertainty regarding profitability remain significant barriers to its adoption. Therefore, dissemination strategies should emphasize cost-benefit analysis, field demonstrations, and gradual integration with conventional fertilizers to strengthen farmers' confidence and accelerate adoption.